2020
DOI: 10.4070/kcj.2019.0099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anticoagulation Intensity in Korean Patients with Atrial Fibrillation: Is It Different from Western Population?

Abstract: Background and Objectives: Although anticoagulation with warfarin is recommended as an international normalized ratio (INR) of prothrombin time between 2.0 and 3.0 and mean time in the therapeutic range (TTR) ≥70%, little has been proven that universal criteria might be suitable in Korean atrial fibrillation (AF) patients. Methods: We analyzed 710 patients with non-valvular AF who took warfarin. INR value and clinical outcomes were assessed during 2-year follow-up. Intensity of anticoagulation was assessed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…A recent Korean experience suggested that mean INR 1.6 to 2.6 was better than mean INR 2.0 to 3.0 for the prevention of both thromboembolism and major bleeding in patients with nonvalvular AF, but did not focus on TTR to substantiate this conclusion. 51 Overall, DOACs in AF patients were associated with a comparable risk of ischemic events and significantly lower risk of major bleeding than warfarin. Therefore, DOACs are the preferred oral anticoagulants over warfarin in AF patients, but ICH risk in Asian patients on the same dose of DOAC (or their associated drug levels) still appeared to be relatively higher compared with non-Asian patients (►Fig.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent Korean experience suggested that mean INR 1.6 to 2.6 was better than mean INR 2.0 to 3.0 for the prevention of both thromboembolism and major bleeding in patients with nonvalvular AF, but did not focus on TTR to substantiate this conclusion. 51 Overall, DOACs in AF patients were associated with a comparable risk of ischemic events and significantly lower risk of major bleeding than warfarin. Therefore, DOACs are the preferred oral anticoagulants over warfarin in AF patients, but ICH risk in Asian patients on the same dose of DOAC (or their associated drug levels) still appeared to be relatively higher compared with non-Asian patients (►Fig.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 91%
“…In patients with atrial fibrillation (AF), warfarin administration is associated with a substantially higher risk of ICH in East Asian patients compared with Caucasian patients, 50,51 resulting in many clinicians adopting a lower international normalized ratio (INR) target range (e.g., INR: 1.6-2.6). However, the evidence for such a lower target INR does not support this approach; in a systematic review and evidence appraisal, lower INR targets reduce bleeding but increase thromboembolism in AF, with similar trends in East Asian and Western studies.…”
Section: Use Of Oral Anticoagulants In East Asiansmentioning
confidence: 99%
“… 19 In a Korean retrospective analysis based on the INR range, major bleeding rate was less developed with a mean INR less than 2.6. 13 However, a dichotomous comparison between an INR of 2.0 to 3.0 and an INR of <2.0 or >3.0 showed a similar major bleeding rate. In the present study, the risk of major bleeding was similar between an INR of 1.6 to 1.99 and an INR of 2.6 to 2.99.…”
Section: Discussionmentioning
confidence: 89%
“… 10 12 A recent Korean retrospective analysis for comparing between low-intensity and standard-intensity anticoagulation with warfarin demonstrated similar clinical outcomes. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Most guidelines suggested optimal level of anticoagulation with vitamin K dependent OACs. [1][2][3][4] Dose titration was done via blood sampling and measurement of serum concentration. Also, serum concentration of vitamin K-dependent OACs was easily changed by daily food or certain medications.…”
mentioning
confidence: 99%